2010
DOI: 10.1111/j.1365-2818.2009.03351.x
|View full text |Cite
|
Sign up to set email alerts
|

ESEM imaging of dynamic biological processes: the closure of stomatal pores

Abstract: Summary Historically, electron microscopy of dynamic biological processes has been impossible to achieve in real time because conventional electron microscopy requires specimen fixation, dehydration and metallic coating. The advent of the environmental scanning electron microscope removes these restrictions, allowing fully hydrated samples to be imaged in their native state. We explore the possibility of secondary electron imaging of biological systems undergoing natural morphological changes in the microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Fig. 4 (in the original paper; McGregor & Donald, 2010) was presented solely an example of beam damage at high magnifications, although stomatal closure in this case occurred simultaneously – the two are not necessarily causally linked, as outlined above. A more extensive study of beam damage in plant tissue in the ESEM – in this case using onion epidermis – has previously been presented in Zheng et al (2009).…”
mentioning
confidence: 87%
“…Fig. 4 (in the original paper; McGregor & Donald, 2010) was presented solely an example of beam damage at high magnifications, although stomatal closure in this case occurred simultaneously – the two are not necessarily causally linked, as outlined above. A more extensive study of beam damage in plant tissue in the ESEM – in this case using onion epidermis – has previously been presented in Zheng et al (2009).…”
mentioning
confidence: 87%
“…The great potential of the ESEM for the investigation of plants was demonstrated in the recent works of Popielarska‐Konieczna et al () focused on the study of the susceptible ECM; Stabentheiner et al () and McGregor and Donald () published results of observation of various plant tissue surfaces, wax and dynamic behavior of plants. The samples were examined in commonly used high‐pressure conditions of the ESEM, with a tendency to cool the samples to a temperature slightly higher than 0°C, with a quite low rate of moisture loss.…”
Section: Introductionmentioning
confidence: 99%
“…and observed by electron irradiation within a vacuum in conventional transmission or scanning electron microscopes. Even though optimum conditions for observation of wet and live samples in the ESEM have been published~Danilatos, 1981a; Stokes, 2006;McGregor & Donald, 2010!, the long-term study of movement in a living animal in an ESEM has not yet been reported. opens a wide field of in situ or dynamic in situ experiments such as growth or reaction processes of nanoparticles in a solution and observation of fully wet and then slowly dried biological materials with minimal treatment.…”
Section: Introductionmentioning
confidence: 99%